SUSTAINABILITY EVALUATION OF BIOSECURITY IMPLEMENTATION ON THE BROILER FARMS IN SELANBAWAK VILLAGE, MARGA DISTRICT, TABANAN REGENCY - SARINI N. P.; N. N. SURYANI; NI PUTU MARIANI; A. A. OKA; M. DEWANTARI (Fakultas Peternakan Universitas Udayana, 2018)
The entry of Avian Influenza (AI) to Indonesia in 2003 gave a tremendously negative impact on poultrybusinesses. Biosecurity is one of the government efforts to protect the spread of infectious diseases to the farms.It gets a good response from all the stakeholders in the poultry industry. Although there are no Avian Influenzaoutbreaks anymore, control to the Highly Pathogenic Avian Influenza (HPAI) is still becoming a main priority incontrolling diseases in the poultry farms. This research was conducted to evaluate the sustainability of biosecurityimplementation in the broiler farms and mentored requirement to prevent AI outbreaks from occurring again.A survey was used to gain information on broiler famers at Selanbawak Village. The samples in this study wereall the farmers who were involved in the ACIAR project AH/2006/169. They had been trained and supervised toimplement biosecurity measures in their farms. The data obtained were descriptive-qualitatively analyzed usingpercentage approach based on the biosecurity implementation criteria. It was found that the biosecurity measuresimplemented by those farmers had not been maintained. Most of the farms were untidy; and rubbishes and busheswere scattered around the farms. The footbath was not properly used as sanitary equipment, and even some wereburied with cement.